Beowulf a translation and commentary : Together with Sellic Spell - Tolkien, J. R. R. 1892-1973 (Houghton Mifflin Harcourt, 2014)
From his creative attention to detail in these lectures there arises a sense of the immediacy and clarity of his vision. It is as if he entered into the imagined past: standing beside Beowulf and his men shaking out their mail shirts as they beached their ship on the coast of Denmark, listening to the rising anger of Beowulf at the taunting of Unferth, or looking up in amazement at Grendel's terrible hand set under the roof of Heorot